Chapter Conclusion - Farrell, John (Taylor & Francis, 2023)
Plato imagined a city with laws and a psychology to replace the heroic ethos, and later Greek authors developed a satiric critique of the heroic character which fed modern literature from More to Voltaire and beyond. The dystopias, real and imagined, of the twentieth century showed how utopia, having summoned the heroes it once banished, could become a fatal instrument in their hands. The utopian wish to escape from politics is another element of this modern problem of agency. The apparently irrepressible character of competitive psychology for many of the writers discussed in these pages may be discouraging, but the moral force of the utopian critique is just as resilient. It may be sobering to consider how serious are the rivals to collective happiness as the aim of social existence; it may be even more sobering to consider how firmly the imagination takes sides.